2011
DOI: 10.1007/s00382-011-1065-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in extratropical storm track cloudiness 1983–2008: observational support for a poleward shift

Abstract: Climate model simulations suggest that the extratropical storm tracks will shift poleward as a consequence of global warming. In this study the northern and southern hemisphere storm tracks over the Pacific and Atlantic ocean basins are studied using observational data, primarily from the International Satellite Cloud Climatology Project, ISCCP. Potential shifts in the storm tracks are examined using the observed cloud structures as proxies for cyclone activity. Different data analysis methods are employed, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
92
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(111 citation statements)
references
References 49 publications
13
92
0
Order By: Relevance
“…S2). There is observational support for the notion that such a shift in storm tracks is associated with positive cloud feedback (54).…”
Section: Discussionmentioning
confidence: 93%
“…S2). There is observational support for the notion that such a shift in storm tracks is associated with positive cloud feedback (54).…”
Section: Discussionmentioning
confidence: 93%
“…Cloud thermodynamic phase affects radiative forcing by modulating absorption of incoming solar radiation, particle evolution, and lifetime (Ehrlich et al, 2008;. Previous satellite observational studies have shown that clouds are shifting poleward in the northern and southern hemispheric extratropical storm tracks (Bender et al, 2012;Marvel et al, 2015;Norris et al, 2016). Within these shifting storm tracks, climate model experiments with forcing from increased CO 2 have shown losses of cloud ice phase and gains of cloud liquid phase McCoy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Wylie et al, 2005;Dim et al, 2011;Bender et al, 2012;Marvel et al, 2015;Norris et al, 2016;Manaster et al, 2017) suggest that climate change signals may be observable within the satellite era. There is a notable absence of published studies regarding trends in ice microphysics.…”
Section: Introductionmentioning
confidence: 99%